Pengembangan Board Game “PlanVest Quest: Build Your Fortune” sebagai Media Pembelajaran Investasi bagi Pemula - M. Mascun Andianto; Suchaina Suchaina; Putri Ayu Anisatus Shalikha (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to develop a board game-based learning media titled "PlanVest Quest: Build Your Fortune" to improve investment literacy among high school students. The background of this research is based on the low level of financial literacy and the lack of interactive learning media in Economics subjects at SMA Negeri 3 Pasuruan. This gamification-based media is designed to make investment learning more interesting, contextual, and enjoyable. The study applies the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. A limited trial was conducted on 10th grade students involving validation by construct and content experts, as well as assessments from teachers and students. The research instrument in the form of a feasibility questionnaire and responses were analyzed descriptively quantitatively. The results showed that PlanVest Quest achieved a very high feasibility level with an expert validation score of 98% and very positive user responses. This media has proven effective in increasing learning motivation, understanding of investment concepts, and students' financial decision-making abilities. Therefore, this media can be used as an innovative alternative in Economics learning at the high school level.